Complete Family Construction for Working Wives in Indonesia and Australia - Nasution, Khoiruddin; Ocktoberrinsyah, Ocktoberrinsyah; Mousa Alzaki, Syah Muhammad (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
Traditional norms in households often assign domestic roles to wives. However, as more wives enter the workforce, these traditional norms must be restructured to foster family resilience. This article presents field research involving 100 working wives in Indonesia and Australia, supplemented with in-depth interviews and Focused Group Discussions (FGD) with 20 working wives and husbands. The collected data were analyzed descriptively using structural-functional theory. The study reveals contrasting dynamics in family responsibilities and the treatment of working wives in Indonesia and Australia. In Indonesia, traditional norms often confine wives to domestic roles, resulting in double burdens and systemic inequality, including domestic violence. In contrast, Australia promotes a more egalitarian approach, supported by strong legal frameworks and a social culture that encourages cooperation in balancing domestic and professional obligations. The study emphasizes that for family balance and stability, both working husbands and wives must respect and collaborate in fulfilling all family roles and functions. These roles should be carried out flexibly, free from rigid gender stereotypes, which is a key to the success of families with working wives. Furthermore, the research highlights the importance of legal reforms and cultural shifts in promoting family equality and preventing domestic violence.